Salt content in ready to eat soups: Comparison between Portugal and Ireland - Fernandes, Paulo (2018)
To compare the salt content of ready to eat soups between a country that is starting to enforce the reduction of salt content in food (Portugal) and a country that already has specific recommendations on salt reduction (Ireland) and also the compliance with EIPAS future goal of 0.2 g of salt/100 g.